The Current State of The Implementation of Mechanisation and Automation (M&A) In Indusrialised Building System (IBS) Construction Industry. - Kamaruddin, Siti Syariazulfa; Mohammad, Mohammad Fadhil; Mahbub, Rohana (Research in Management of Technology and Business, 2021)
Integrating Mechanisation and Automation (M&A) in the construction process is necessary to less dependency on labour, reduce production time and costs, improve working conditions, avoiding dangerous works, allow work to be performed where people cannot do, and eventually will increase performance, and product quality. This study discusses the current state in the implementation of M&A in the Industrialised Building System (IBS) approach. The sustainability principles in the IBS have always maintained the harmony between environment and construction, improve human self-respect, and encourage economic development to strive for a Sustainable Development Goal agenda. The findings of the study provide an insight into the implementation of M&A on the ways of looking forwards to industrialisation in order to create sustainability in IBS construction.